The "Racial Welfare" State and its Political and Religious Enemies. Research Notes on the Gestapo Files from the Beginning of the Nazi Dictatorship (1933-1937) (2014)
The main problem of this paper is the relationship between the actions of Die Geheime Staatspolizei (Gestapo), the generation and maintenance of an order that had to eliminate and neutralize the “enemies” of the “German people” -Communists and the Catholi